Lenvatinib-Associated Cervical Artery Dissections in a Patient with Radioiodine-Refractory Metastatic Papillary Thyroid Carcinoma - Groden, Phillip J.; Lee, Thomas C.; Bhattacharyya, Shamik; Connors, Jean; Lorch, Jochen (Frontiers in Medicine, 2018)
Lenvatinib is a tyrosine kinase inhibitor (TKI) approved by the FDA for the treatment of radioiodine-refractory (RAIR) thyroid cancers. Side effects can be severe, however, and include headaches, hypertension, arterial and venous thromboembolic events, and fatalities. Cervical artery dissections (CAD) are leading contributors of cerebral ischemia in young adults, yet the pathophysiology is poorly understood. Here we describe a case of a 34-year old female with recurrent, metastatic, RAIR papillary thyroid cancer who, following her second week of lenvatinib treatment, developed significant CAD which resolved following the termination of the TKI therapy. Given the lack of risk factors for the disorder in the patient’s history, the known cardiovascular events associated with the drug, previously described cases of arterial dissections linked to VEGF-inhibitors, and the temporal relationship between the onset of symptoms and the treatment start date, a causal relationship between the CAD and lenvatinib is suggested.